135k views
5 votes
F(x) = 3x - 7 and g(x) = -2x - 6. Find (f o g)(4)

User Curunir
by
4.9k points

1 Answer

6 votes

Answer:

(f o g)(4) = - 49

Explanation:

F(x) = 3x - 7

g(x) = -2x - 6

To find (f o g)(4) we must first find (f o g)(x)

To find (f o g)(x) substitute g(x) into f(x) that's for every x in f (x) replace it with

g (x).

We have

(f o g)(x) = 3( - 2x - 6) - 7

= - 6x - 18 - 7

We have

(f o g)(x) = - 6x - 25

To find (f o g)(4), substitute the value of x that's 4 into (f o g)(x)

We have

(f o g)(4) = - 6(4) - 25

= - 24 - 25

We have the final answer as

(f o g)(4) = - 49

Hope this helps you

User Niels Bosma
by
5.7k points